2021
DOI: 10.1038/s41598-021-91546-z
|View full text |Cite
|
Sign up to set email alerts
|

Decoding empagliflozin’s molecular mechanism of action in heart failure with preserved ejection fraction using artificial intelligence

Abstract: The use of sodium-glucose co-transporter 2 inhibitors to treat heart failure with preserved ejection fraction (HFpEF) is under investigation in ongoing clinical trials, but the exact mechanism of action is unclear. Here we aimed to use artificial intelligence (AI) to characterize the mechanism of action of empagliflozin in HFpEF at the molecular level. We retrieved information regarding HFpEF pathophysiological motifs and differentially expressed genes/proteins, together with empagliflozin target information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…This decision was made, first, according to the paradigm of role of inflammation and oxidative stress in HFpEF, where SGLT2i can benefit through the blockade of NH1 receptors. 43 Second, it was shown that SGLT2i improves the diastolic function of the LV and the LV mass index. 44 We also had data from the SOLOIST-WHF study, where sotagliflozin was shown to have a beneficial effect, although 20.1% of patients had LVEF>50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decision was made, first, according to the paradigm of role of inflammation and oxidative stress in HFpEF, where SGLT2i can benefit through the blockade of NH1 receptors. 43 Second, it was shown that SGLT2i improves the diastolic function of the LV and the LV mass index. 44 We also had data from the SOLOIST-WHF study, where sotagliflozin was shown to have a beneficial effect, although 20.1% of patients had LVEF>50%.…”
Section: Discussionmentioning
confidence: 99%
“…Our study included patients regardless of LVEF. This decision was made, first, according to the paradigm of role of inflammation and oxidative stress in HFpEF, where SGLT2i can benefit through the blockade of NH1 receptors 43. Second, it was shown that SGLT2i improves the diastolic function of the LV and the LV mass index 44.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, big data analysis using deep learning artificial intelligence seems to be a reasonable approach to reveal the most likely targets. An algorithm that analyzed publicly available databases showed that empagliflozin could reverse 59% of all known protein alterations in heart failure with preserved ejection fraction (HFpEF) with a predominance of the effect via the sodium hydrogen antiporter 1 (NHE1) receptor and the impact on oxidative stress modulation, myocardial stiffness, myocardial extracellular matrix remodeling, and systemic inflammation [102]. None such analysis has been performed for another SGLT2 inhibitor so far.…”
Section: Molecular Research Of Sglt2 Inhibitors Connected To Arrhythmiasmentioning
confidence: 99%
“…Increasing evidence supports SGLT2is' inhibition of NHE1 in the heart, either directly and/or indirectly, explaining some of the cardioprotective mechanisms in HFpEF ( Figure 2 ). [ 38 , 109 , 110 ] Enhanced activity of NHE1 has been detected in HFpEF pathology, such as in pressure overload and hypertensive hypertrophy. [ 111 – 113 ] When pathologically activated in cardiomyocytes, NHE1 exchanges hydrogen for an intrusion of sodium with reversal of the Na + /Ca2 + exchanger, resulting in sodium-dependent calcium overload, pH alterations and oxidative stress.…”
Section: Proposed Mechanisms Of Action Of Sglt2is In Hfpefmentioning
confidence: 99%
“…[ 114 ] A mechanistic study using artificial intelligence also showed empagliflozin-mediated NHE1 inhibition appears to modulate cardiomyocyte stiffness, myocardial extracellular matrix remodelling, systemic inflammation and concentric hypertrophy mechanisms. [ 110 ] Validation of the data was performed by measuring declining plasma concentrations of inducible nitric oxide synthase, NLR family pyrin domain containing 3 inflammasome and TGF-β1 during 12 months of empagliflozin treatment. [ 110 ]…”
Section: Proposed Mechanisms Of Action Of Sglt2is In Hfpefmentioning
confidence: 99%